Variations in the extensor indicis proprius muscle in the Burmese population: implications for hand reconstructive surgery - Saung A Kari; Pedzisai Mazengenya; Arthur Tsalani Manjatika; Tin Moe Nwe; Zaw Myo Hein (Elsevier, 2023)
Background: The use of extensor indicis proprius (EIP) muscle tendon for tendon grafting and transplantation in the management of hand injuries is common. Anatomical variations of the EIP tendons have been reported with variable prevalence and presentation in different populations worldwide. Knowledge of possible variation patterns is crucial in reconstructive surgery. The current study aims to describe the prevalence of anatomical variations of the EIP in the Burmese population. Methods: A total of 50 cadavers (39 males, and 11 females) were dissected. Both upper limbs of each cadaver were observed. The presence of the EIP, the number of tendons, the origin and insertion of the muscle and its relation with the extensor digitorum communis (EDC) were recorded and variations reported. Results: Of the 100 limbs studied in the 50 cadavers, only 1/100 limb was reported to have an absent EIP muscle and tendon. Of the remaining 99/100 limbs examined, one of them consists of a double tendon, that is, EIP and extensor indicis et medii communis (EIMC) were inserted separately onto the index finger and middle finger respectively on the dorsum of the left hand. Further to this, there is one case in which an extra muscle belly was observed in the EIP tendon, this muscle is commonly known as the extensor digitorum brevis manus muscle. All the EIP variations were observed in the male cadavers only. Conclusion: Of the 50 cadavers studied, 3/100 limbs exhibited EIP variations in the current studied population. Population-specific studies on these variations may aid in a better understanding of the different anatomical patterns of the muscles in the dorsum of the hand. This may lead to improved diagnosis and surgical management of injuries to the dorsum of the hand and for the use of the EIP tendon in surgical grafts and transplantations.